Il triangolo non l’avevo considerato. Metafora, immagini mentali e proposizioni tra Relevance Theory e Perceptual Symbol Theory - Carapezza, Marco; Garello, Stefania (Rivista Italiana di Filosofia del Linguaggio, 2020)
In this paper we will show the need for a multimodal approach to the study of metaphorical utterances. We will discuss this hypothesis showing potentials and limits of the metaphor studies conducted within Relevance Theory, which has represented the most authoritative and radical theoretical framework based on the propositional character of metaphorical utterances. In particular, we will focus on the last papers by Carston (2010, 2018), in which it is recognized that the comprehension of complex and poetic metaphors could involve the activation of mental images. We will discuss the problem that the notion of mental imagery poses to Relevance Theory and we will try to overcome these problems by an hybridization between Relevance Theory and Perceptual Symbol Theory. Then, we will suggest that local and novel metaphors, such as “love is fresh fruit”, could require the activation of mental imagery too and we will characterize this kind of metaphor in terms of compresence of narrowing, broadening and conscious experience of a multimodal mental image.